Photocatalytic Mineralization of Azure A Using Li2CuMo2O8 Nanoparticles - Joshi M.; Kumawat P.; Ameta R.; Ameta S.C. (International Journal of Research in Chemistry and Environment (IJRCE), 2015)
Photocatalytic mineralization of azure A was studied using lithium copper molybdate as photocatalyst. The effect of different variables like pH, concentration of dye, amount of semiconductor and light intensity was observed. The photo degradation efficiency of the catalyst for the azure A was found to be 72.08 %. Under optimal conditions the rate constant k was 2.47 x 10-4 sec-1. Dye was mineralized on photocatalytic degradation into smaller ions like NO3- and SO42-.Water quality parameters like pH, COD, TDS, salinity, conductivity and DO were observed before and after treatment. It was observed that photocatalytic degradation affect these parametersfavourably. A tentative mechanism for photocatalytic degradation of azure A, involving OH radical as an active oxidizing species, has also been proposed.